2003
DOI: 10.1002/jcp.10276
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion‐dependent control of Akt/protein kinase B occurs at multiple levels

Abstract: The protein kinase Akt, also known as Protein Kinase B, has been implicated in the survival of several cell types challenged with various apoptotic stimuli. In CCL39 lung fibroblasts, apoptosis is induced by anchorage and mitogen removal. Mitogeninduced activation of Akt is highly anchorage dependent in these cells and removal of adhesion is accompanied by a rapid loss in responsiveness to soluble agonists followed by a significant decrease in Akt abundance. Loss of the protein appears to be independent of kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Decreased Akt activity has been reported in anoikis (3), and inhibition of Akt increases cell susceptibility to Fas-mediated apoptosis (1). Recent studies have demonstrated that there is activation of PI3-kinase following integrin engagement (23) and, conversely, that there is decreased Akt activity following disruption of cell anchorage (39). We observed decreased levels of phosphorylated epithelial Akt following neutrophil transmigration across epithelia as well as following epithelial incubation with leukocyte elastase for 18 h. These decreased levels may be partly attributable to disruption in cell adhesion.…”
Section: Discussionmentioning
confidence: 97%
“…Decreased Akt activity has been reported in anoikis (3), and inhibition of Akt increases cell susceptibility to Fas-mediated apoptosis (1). Recent studies have demonstrated that there is activation of PI3-kinase following integrin engagement (23) and, conversely, that there is decreased Akt activity following disruption of cell anchorage (39). We observed decreased levels of phosphorylated epithelial Akt following neutrophil transmigration across epithelia as well as following epithelial incubation with leukocyte elastase for 18 h. These decreased levels may be partly attributable to disruption in cell adhesion.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are consistent with our previous observations in fibroblasts that removing serum survival factors can potentiate anoikis. 45 …”
Section: Effects Of S 36578-2 On Nonimmortalized Microvascular-derivementioning
confidence: 99%
“…Upon b-estradiol stimulation, DRaf:ERs have been shown to specifically activate the downstream targets of Raf molecule, MEK1/2 and ERK1/2 (McCubrey et al, 1998;Hoyle et al, 2000). This system has been exploited successfully and extensively by others to study the roles of Raf in cancer biology (McCarthy et al, 1997;McCubrey et al, 1998;Hoyle et al, 2000;Chang and McCubrey, 2001;Le Gall et al, 2003).…”
Section: Introductionmentioning
confidence: 99%